Heat Transfer Enhancement of Energy Pile with Nanofluids as Heat Carrier - Ruizhi Wang; Ya Yin; Qingwen Li; Xiao Hai; Naifu Deng; Chao Huang (Advances in Civil Engineering)
As one of the core components of the transport medium in the energy pile system, the circulating working fluid is crucial for the enhancement of its heat transfer efficiency. In this study, based on the heat transfer enhancement theory of nanofluids, deionized water was used as the base solution to prepare the corresponding 0, 0.5, 1, and 1.5 vol% nanofluids by introducing nanoparticles SiO2, Al2O3, CuO, and Cu. The laws of thermal conductivity and specific heat capacity with the volume fraction of different nanofluids are studied by the comparison. The results of thermal conductivity research illustrate that the specific heat capacity of nanofluids decreases linearly with the increase of the volume concentration of nanoparticles, but the thermal conductivity increases linearly. The fluid with the highest thermal conductivity and specific heat capacity is Cu–water nanofluids. In addition, it is proposed to directly apply all kinds of nanofluids with 1 vol% as circulating fluid to self-made miniature model box of energy pile to simulate the working conditions in summer. The influence laws of the nanofluids on the flow rate and heat transfer efficiency in the energy pile were calculated through the temperature difference between the inlet and outlet of the heat exchange tube. The results reveal that the nanofluids used in the experiment exert a optimization influence on the heat transfer of energy pile but the mass flow rate of the nanofluids during the circulation is decreased compared with that of the deionized water circulation liquid. Among them, the temperature difference between inlet and outlet of Cu–water nanofluid is the largest, which has the best effect on improving the heat transfer efficiency of the energy pile but its mass flow loss is also the largest. The research results can provide a reliable reference for the improvement of heat transfer efficiency of energy pile engineering in the future.